2022
DOI: 10.1021/acs.inorgchem.2c02508
|View full text |Cite
|
Sign up to set email alerts
|

Metallacyclosilanes of Calcium, Yttrium, and Iron

Abstract: Utilizing a choice of α,ω-oligosilanylene diides, it is possible to synthesize a number of heterocyclosilanes with heteroelements of calcium, yttrium, and iron by metathesis reactions with respective metal halides CaI2, YCl3, and FeBr2. 29Si NMR spectroscopic analysis of the calcacyclosilanes suggests that these compounds retain a strong oligosilanylene dianion character, which is more pronounced than in the analogous magnesacyclosilanes. As the electronegativity of calcium lies between potassium and magnesium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…6 Schumann reported the first Ln( iii ) examples, [Li(DME) 3 ][Ln(Cp) 2 (SiMe 3 ) 2 ] (Ln = Dy, Ho, Er, Tm, Lu), in the late 1980s; 16–18 since then, other Ln( iii ) Cp-supported silanide complexes have included [Ln(C 5 Me 4 R) 2 {SiH(SiMe 3 ) 2 }] (R = Me; Ln = Sc, Y, Nd, Sm, R = Et; Ln = Nd, Sm) by Tilley and Rheingold, 19,20 [Lu(Cp*) 2 {SiH 2 ( o -MeOC 6 H 4 )}] (Cp* = {C 5 Me 5 }) by Castillo and Tilley, 8 [K(2.2.2-crypt)][Y(C 5 H 4 Me) 3 (SiH 2 Ph)] by Evans, 21 and a series of [Ln(Cp) 3 (SiR 3 )] − anions (Ln = La, Ce; SiR 3 = Si(H)Mes 2 , Si(H)Ph 2 , Si(Me)Ph 2 , SiPh 3 ; Mes = C 6 H 2 Me 3 -2,4,6) by Fang; 22 Baumgartner and Marschner have reported a wide variety of this class of complex, including [K 2 (18-crown-6) 2 Cp][Ln(Cp) 2 {[Si(SiMe 3 ) 2 SiMe 2 ] 2 }] (Ln = Tm, Ho, Tb, Gd), 23 [K(18-crown-6)][Ln(Cp) 3 {Si(SiMe 3 ) 3 }] (Ln = Ho, Tm) and [{K(18-crown-6)} 2 Cp][Ln(Cp) 3 {Si(SiMe 3 ) 3 }] (Ln = Ce, Sm, Gd, Tm), 24 and the Y( iii ) complexes [K(DME) 4 ][Y(Cp) 2 (L)] (L = {[Si(SiMe 3 ) 2 SiMe 2 ] 2 O} 25 or {[Si(SiMe 3 ) 2 SiMe 2 ] 2 }). 26 Reports of complexes that contain structurally authenticated Cp-supported An–Si bonds are currently limited to the U( iii ) silylenes [U(Cp′) 3 {Si(NMe 2 )[PhC(N t Bu) 2 ]}] (Cp′ = {C 5 H 4 SiMe 3 }) and [U(Cp′) 3 {Si[PhC(N i Pr) 2 ] 2 }] by Arnold, 27 and the An( iv ) silanides [An(Cp′) 3 {Si(SiMe 3 ) 3 }] (An = Th, U) by some of us; 28 Porchia, 29 Tilley, 30 and Marks 31 have all reported examples of An silanide complexes that were not characterised in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…6 Schumann reported the first Ln( iii ) examples, [Li(DME) 3 ][Ln(Cp) 2 (SiMe 3 ) 2 ] (Ln = Dy, Ho, Er, Tm, Lu), in the late 1980s; 16–18 since then, other Ln( iii ) Cp-supported silanide complexes have included [Ln(C 5 Me 4 R) 2 {SiH(SiMe 3 ) 2 }] (R = Me; Ln = Sc, Y, Nd, Sm, R = Et; Ln = Nd, Sm) by Tilley and Rheingold, 19,20 [Lu(Cp*) 2 {SiH 2 ( o -MeOC 6 H 4 )}] (Cp* = {C 5 Me 5 }) by Castillo and Tilley, 8 [K(2.2.2-crypt)][Y(C 5 H 4 Me) 3 (SiH 2 Ph)] by Evans, 21 and a series of [Ln(Cp) 3 (SiR 3 )] − anions (Ln = La, Ce; SiR 3 = Si(H)Mes 2 , Si(H)Ph 2 , Si(Me)Ph 2 , SiPh 3 ; Mes = C 6 H 2 Me 3 -2,4,6) by Fang; 22 Baumgartner and Marschner have reported a wide variety of this class of complex, including [K 2 (18-crown-6) 2 Cp][Ln(Cp) 2 {[Si(SiMe 3 ) 2 SiMe 2 ] 2 }] (Ln = Tm, Ho, Tb, Gd), 23 [K(18-crown-6)][Ln(Cp) 3 {Si(SiMe 3 ) 3 }] (Ln = Ho, Tm) and [{K(18-crown-6)} 2 Cp][Ln(Cp) 3 {Si(SiMe 3 ) 3 }] (Ln = Ce, Sm, Gd, Tm), 24 and the Y( iii ) complexes [K(DME) 4 ][Y(Cp) 2 (L)] (L = {[Si(SiMe 3 ) 2 SiMe 2 ] 2 O} 25 or {[Si(SiMe 3 ) 2 SiMe 2 ] 2 }). 26 Reports of complexes that contain structurally authenticated Cp-supported An–Si bonds are currently limited to the U( iii ) silylenes [U(Cp′) 3 {Si(NMe 2 )[PhC(N t Bu) 2 ]}] (Cp′ = {C 5 H 4 SiMe 3 }) and [U(Cp′) 3 {Si[PhC(N i Pr) 2 ] 2 }] by Arnold, 27 and the An( iv ) silanides [An(Cp′) 3 {Si(SiMe 3 ) 3 }] (An = Th, U) by some of us; 28 Porchia, 29 Tilley, 30 and Marks 31 have all reported examples of An silanide complexes that were not characterised in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…For yttrium silicon chemistry, structurally authenticated complexes containing Y–Si bonds that have been reported to date include [Y­(Cp*) 2 {SiH­(SiMe 3 ) 2 }] (Cp* = C 5 Me 5 ), [Y­{Si­(SiMe 3 ) 2 R}­(I) 2 (THF) 3 ] (R = Et or SiMe 3 ), [Y­{Si­(SiMe 2 H) 3 } 2 (OEt 2 )­(μ 2 -Cl) 2 (μ 3 -Cl)­K 2 (OEt 2 ) 2 ] ∞ , [K­(2.2.2-crypt)]­[Y­(C 5 H 4 Me) 3 (SiH 2 Ph)], [K­(DME) 4 ]­[Y­(L) (A) 2 (DME) n ] (L = {[Si­(SiMe 3 ) 2 SiMe 2 ] 2 O}, A = Cp, n = 0, or A = Cl, n = 1; L = {[Si­(SiMe 3 ) 2 SiMe 2 ] 2 }, A = Cp, n = 0, or A = Cl, n = 1), [Y­(Cp) 3 {Si­[{N­(CH 2 t Bu)} 2 C 6 H 4 -1,2]}], 19 and [Y­{N­(SiHMe 2 ) 2 } 3 {Si­[(N t Bu) 2 CPh]­[C 5 H 4 N­(NMe-2)]-κ 2 Si , N }] . Recently, we showed that a combination of 29 Si­{ 1 H} NMR spectroscopy and density functional theory (DFT) calculations could be applied to quantify covalency in diamagnetic Yb­(II)–Si bonds, allowing comparisons with Mg­(II), Ca­(II), and in silico -calculated No­(II) homologs .…”
Section: Introductionmentioning
confidence: 99%
“…7 It should be noted here that Scheme 1 Synthesis of 2. despite the difference in the coordination geometry around the iron center, the Fe-Si bond lengths (2.5385(4) Å) are comparable to those found in precursor 1 (2.5445(8) Å) 4a as well as those in the iron(II) bis(silyl) complex [(SiMe 3 ) 2 SiSiMe 2 OSiMe 2 Si(SiMe 3 ) 2 ]Fe(THF) 2 , which has recently been reported by Marschner et al (2.494 Å). 8 In addition, a cobalt complex, trans-(NHC) 2 Co[Si(H)Ph 2 ] 2 , the structure of which is relevant to complex 2, was recently reported by Deng and co-workers. 9 Complex 2 is paramagnetic, and its 1 H NMR spectrum in C 6 D 6 at room temperature exhibits a signal at 5.00 ppm for SiMe 3 as well as resonances at −46.24 and 16.10 ppm for the methyl group of the MeIM Me ligands.…”
Section: Synthesis Of Trans-(meimmentioning
confidence: 92%